2020
DOI: 10.13005/ojc/360120
|View full text |Cite
|
Sign up to set email alerts
|

TiO2NPs Embedded in Chitosan Membrane for Efficient Photodegradation of Various Dyes

Abstract: Synthesis of a new chitosan/TiO 2 NPs nanocomposite was conducted, TiO 2 was used as photocatalyst in combination with chitosan which act as co-adsorbent and an immobilization agent. They were used under UV source for photodegradation of anionic and cationic, as well as for removing neutral dyes dissolved in water. Several techniques like scanning electron microscope (SEM) and energy-dispersive X-ray (EDAX) spectroscopy, together with Fourier-transform infrared spectroscopy (FT-IR) analysis and swelling ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The detection limit of ammonia in the present study is lower than the reported methods. 1,[31][32][33][34][36][37][38][39] Most reports do not provide visual detection 1,[30][31][32][33][34]36,39 or clear color differentiation. 35,38 In the present study, the color changes of the sensor in the absence and presence of different ammonia concentrations are completely different and can be easily detected by the naked eye.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection limit of ammonia in the present study is lower than the reported methods. 1,[31][32][33][34][36][37][38][39] Most reports do not provide visual detection 1,[30][31][32][33][34]36,39 or clear color differentiation. 35,38 In the present study, the color changes of the sensor in the absence and presence of different ammonia concentrations are completely different and can be easily detected by the naked eye.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…However, in the current research, there is no need to modify or functionalize the surface of the nanoparticles. Moreover, some reports are based on specic fruits and plants, 31,33,36 which are only cultivated in a few countries. Therefore, they are expensive and not available.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%